Factors Associated with Persistence with Teriparatide Therapy: Results from the DANCE Observational Study - Deborah T. Gold; David L. Weinstein; Gerhardt Pohl; Kelly D. Krohn; Yi Chen; Eric S. Meadows (Journal of Osteoporosis)
Purpose. Determine patient-reported reasons for discontinuation with teriparatide. Methods. Patients taking teriparatide in a multicenter, prospective, and observational study were given three questionnaires: baseline, follow-up questionnaire 1 (QF1, 2 to 6 months), and follow-up questionnaire 2 (QF2, 12 months). Discontinuation reported at QF1 and QF2 was defined as “early” and “late,” respectively, and remaining patients were considered persistent. Cochran-Armitage trend test was used to identify factors associated with discontinuation. Results. Side effects, concern about improper use, injection difficulties, and several patient-perceived physician issues were associated with early discontinuation. Low patient-perceived importance of continuing treatment, side effects, difficulty paying, and low patient-perceived physician knowledge were associated with late discontinuation. The most common specific reasons selected for discontinuing treatment were “concerns about treatment outweighing the benefits” (n=53) and “difficulty paying” (n=47). Conclusions. Persistence with teriparatide is dependent on managing side effects, addressing financial challenges, proper training, and obtaining support from the healthcare provider.